2010
DOI: 10.1111/j.1741-2358.2009.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the efficacy of ultrasonic waves in removing biofilms

Abstract: This study demonstrated that ultrasonic wave exposure in a non-contact mode effectively removed adherent biofilms composed of S. mutans in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Furthermore, multiple factors affect the activity of UTMDemediated HBD-3 against biofilms infections. First, the US parameters, including acoustic intensity, frequency, duty cycle, and duration, are significant [35]. A high power and long durations of exposure were sufficient to destroy the biofilms but these conditions may cause tissue damage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple factors affect the activity of UTMDemediated HBD-3 against biofilms infections. First, the US parameters, including acoustic intensity, frequency, duty cycle, and duration, are significant [35]. A high power and long durations of exposure were sufficient to destroy the biofilms but these conditions may cause tissue damage [30].…”
Section: Discussionmentioning
confidence: 99%
“…The level of shear stress is largely dependent on US parameters [27], and we can adjust it with an acoustic pressure between 100 Pa and 1000 Pa [28]. According to Williams and Pitt [8], there appears to be an intensity threshold (between 100 and 10 mW/cm 2 ) below which ultrasound may not enhance the bactericidal effect of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…25 Phull et al showed that ultrasound is suitable for water desinfection, whereas ultrasound at high frequencies seemed to be more effective with regards to bactericidal effects. 30 Nishikawa et al demonstrated that Staphylococcus mutans biofilm can be effectively removed by ultrasonic exposure 31 in an in vivo model, and Xu et al demonstrated that high-intensity focused ultrasound is able to destroy Pseudomonas aeruginosa biofilm. 32 In contrast to that, Ensing et al showed that ultrasound alone did not negatively significantly affect bacterial viability (Escherichia coli, Staphylococcus aureus, coagulase negative staphylococci, Pseudomonas aeruginosa), neither planktonically nor in a biofilm.…”
Section: Discussionmentioning
confidence: 99%